DEFENDING AGAINST SOCIAL MEDIA: HOW PUBLIC CRIMINAL DEFENSE HELPS US ADDRESS SOCIAL MEDIA GOVERNANCE - Lane, Jeffrey; Ramirez, Fanny Anne; Patton, Desmond Upton (AoIR Selected Papers of Internet Research, 2020)
As justice-minded academics, we want to understand the role of social media in civil society with a vested interest in ensuring that social media serves a pluralistic society fairly and equitably. Gillespie (2018) has helped frame this task in terms of both governance of platforms and by platforms, but we also want to know what state governments do with social media (Gorwa, 2019). This paper focuses on how social media companies cooperate with state governments to hold users criminally liable, and the lessons this case bears for understanding and improving the fairness and equity of judicial governance. We draw on interviews with twenty public criminal defenders in NYC in which we asked: 1) where social media appears in their cases and the role it plays; 2) their access to user content and social media companies; and, 3) how they use social media as evidence and defend against it. We identified three problem areas around fair and equal access to the law. First, we heard concerns that the cooperation of social media companies was asymmetrical because companies worked almost exclusively with law enforcement. Second, public defenders were upset about overly broad search warrants that furnished the full contents of a suspect’s social media account. Third, public defenders complained about the use and admission of prejudicial evidence that played to negative, racial stereotypes of their clients. We suggest several reforms for judicial governance, including more nearly equitable cooperation practices, restrictions on search warrants, and admissibility protocols and disclaimers on admitted materials.